Transcriptional profiles of non-neuronal and immune cells in mouse trigeminal ganglia - Mecklenburg, Jennifer; Shein, Sergey A.; Malmir, Mostafa; Hovhannisyan, Anahit H.; Weldon, Korri; Zou, Yi; Lai, Zhao; Jin, Yu-Fang; Ruparel, Shivani; Tumanov, Alexei V.; Akopian, Armen N. (Frontiers in Pain Research, 2023)
Non-neuronal cells constitute 90-95% of sensory ganglia. These cells, especially glia and immune cells, play critical roles in the modulation of sensory neurons. The aim of this review-study was to identify, profile and summarize trigeminal (TG) non-neuronal cell types in naïve male mice using published and our single-cell RNA sequencing (scRNA-seq), flow cytometry and immunohistochemistry (IHC) data. TG contains 5 types of non-neuronal cells: glial, fibroblasts, smooth muscle, endothelial and immune cells.There is an agreement among publications for glial, fibroblasts, smooth muscle and endothelial cells.Based on gene profiles, glial cells were classified as myelinated and unmyelinated Schwann cells and satellite glial cells (SGC). Mpz has dominant expression in Schwann cells, and Fabp7 is specific for SCG. Two types of Col1a2 + fibroblasts located throughout TG were distinguished. TG smooth muscle and endothelial cells of blood vessels were detected using well-defined markers. Our study reported 3 types of macrophages (Mph) and 4 types of neutrophils (Neu) in TG. Mph were located among neuronal bodies and nerve fibers, and were sub-grouped by unique transcriptomic profiles with Ccr2, Cx3cr1 and Iba1 as markers. Comparison with databases showed that Mph-1 is similar to choroid plexus-low (CP lo ) border-associated macrophages (BAM). Mph-2 has the highest prediction score with CP hi BAM, while Mph-3 is distinct. S100a8 + Neu were located in dura surrounding TG and were sub-grouped by clustering and expressions of Csf3r, Ly6G, Ngp, Elane and Mpo. Integrative analysis of published datasets indicated that Neu-1, -2, -3 are similar to the brain neutrophil-1 group, while Neu-4 has a resemblance to monocyte-derived cells. Overall, the generated and summarized datasets on non-neuronal TG cells showed a unique composition of myeloid cell types in TG and could provide essential and fundamental information for studies on cell plasticity, interactomic networks between neurons and non-neuronal cells and function during variety of pain conditions in the head and neck region.